Indigenous women leading the defence of human rights from the abuses by mega-projects in Latin America, in the face of extreme violence - Tapias Torrado, NR (2020)
In the face of extreme violence, some Indigenous women-led social movement organisations defending human rights from the abuses related to mega-projects have achieved favourable changes in corporate practices. In the predominantly patriarchal, capitalist and racist context of Latin America, what explains the success (or not) of Indigenous women-led mobilisations regarding the most politically and economically powerful actors? Although there is a well-established literature on social movements, some dedicated to the influence on corporate practices, there is a lacuna concerning the agency, leadership and impact of Indigenous women-led movements in the context of mega-projects.